Internalisasi Nilai-Nilai Syariah dalam Perilaku Konsumtif Mahasiswa Muslim: Studi Kasus di Perguruan Tinggi Islam - Munawaroh, Ma’rifatul (CV. Lentera Literasi Indonesia, 2025)
This study aims to examine the process of internalizing sharia values in the consumptive behavior of Muslim students at Islamic universities in Banyuwangi. This research employs a qualitative approach using a case study method. Data collection techniques include observation, in-depth interviews, and documentation. The research subjects consist of students, lecturers, and campus figures involved in religious guidance. The findings reveal that the internalization of sharia values in student consumption behavior occurs through three stages: value cognition, value appreciation, and value actualization. Although most students understand Islamic financial principles such as the prohibition of excessiveness (israf), the importance of qana’ah (contentment), and the pursuit of blessings (barakah) in wealth management consumptive behavior is still present due to the influence of social media, peer pressure, and a digital consumer culture. A religious campus environment, the role of lecturers, and Islamic student organizations have proven to play a significant role in supporting the internalization process of these sharia values. This study recommends strengthening practical-based Islamic economic character education so that sharia values are not only understood theoretically but are also reflected in the students’ real-life behavior.